Systems perspectives on transforming Swiss housing by 2040: wellbeing, shared spaces, sufficiency, and de-sprawl - Nick, Sascha (Frontiers in Sustainability, 2024)
The Swiss habitat–buildings and related mobility–faces multiple interconnected problems which can only be solved together. These include high energy consumption, significant climate impact, excessive material use with low circularity, accelerating urban sprawl and ecosystem destruction, high mobility costs, low inclusion, and mixed wellbeing outcomes. Guided by values of wellbeing for all within planetary boundaries, we propose a normative scenario based on a nationwide moratorium on new construction until 2100, coupled with four simultaneous neighborhood-scale interventions: renovating buildings to achieve energy class A with high indoor environmental quality, creating flexible shared living spaces, ensuring essential daily services are available within each neighborhood, and deconstructing unneeded settlements. Action levers, coordinated efforts on multiple system leverage points, are here combined with rethinking needs satisfiers. Our model predicts that full renovation could be accomplished in 14-18 years, significantly reducing labor, energy, materials, and costs both during and after the transition. Furthermore, it could reverse urban sprawl to levels seen in 1935 or even 1885, depending on deconstruction choices. These findings suggest that demand-side policies could be implemented with low risk, enhancing wellbeing, energy resilience, biodiversity, and climate action, thus providing a strong foundation for societal dialogue and experimentation.